2024
DOI: 10.3390/vetsci11020064
|View full text |Cite
|
Sign up to set email alerts
|

First-Intention Incisional Wound Healing in Dogs and Cats: A Controlled Trial of Dermapliq and Manuka Honey

Pagona G. Gouletsou,
Theodora Zacharopoulou,
Vassilis Skampardonis
et al.

Abstract: This study aimed to compare incisional wound healing in cats and dogs after the topical application of Μanuka honey and a new medical device, Dermapliq. Comparisons were made between each treatment and control, between the two treatments, and between dogs and cats. Twelve cats and twelve dogs were included in this study, and the impact of the two substances was examined through cosmetic, clinical, ultrasonographical, and histological evaluation. The use of Dermapliq in first-intention wound healing achieved a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…Suture removal times varied according to the age of the patient at the time of the intervention, potentially due to immune system maturation and body condition, with older animals often presenting better body condition [ 36 ]. Comparative studies between cats and dogs revealed differences in healing times, possibly due to anatomical factors such as cutaneous angiogenesis and the number of perforating vessels, with cats presenting a slower healing process [ 32 , 40 , 41 , 42 , 43 , 44 , 45 ]. While the surgery recovery time and suture removal time may not be directly related to the surgical technique itself, they serve as important indicators of the overall success of the surgical intervention and postoperative management.…”
Section: Discussionmentioning
confidence: 99%
“…Suture removal times varied according to the age of the patient at the time of the intervention, potentially due to immune system maturation and body condition, with older animals often presenting better body condition [ 36 ]. Comparative studies between cats and dogs revealed differences in healing times, possibly due to anatomical factors such as cutaneous angiogenesis and the number of perforating vessels, with cats presenting a slower healing process [ 32 , 40 , 41 , 42 , 43 , 44 , 45 ]. While the surgery recovery time and suture removal time may not be directly related to the surgical technique itself, they serve as important indicators of the overall success of the surgical intervention and postoperative management.…”
Section: Discussionmentioning
confidence: 99%